2021
DOI: 10.9734/jpri/2021/v33i64a35318
|View full text |Cite
|
Sign up to set email alerts
|

A Study Protocol for Estimating the Association of De Ritis ratio (AST/ALT) with Outcomes in Patients of Acute Ischemic Stroke

Abstract: Background: One of the clinical endpoints of atherosclerosis is stroke, the most prominent clinical manifestation of cerebrovascular disease. It is a cerebral blood vessel disease that nourishes the brain. A global health concern is stroke. It is the second most prevalent cause of death worldwide and the fourth leading cause of disability. The underlying pathophysiology in most ischemic strokes is atherosclerosis. Few studies have shown that high AST/ALT ratio was independently corelated with the  increased da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There was no significant association of calcium with NIHSS and Barthel Index as noted by Sivasubramaniyam et al in 2017. Ishfaq et al in their study of 138 patients revealed that low levels of serum calcium may be related to more severe clinical findings at the stroke onset [ 14 , 17 ]. A study by Borah et al revealed that total calcium, albumin-corrected calcium, and ionized calcium had a statistically significant negative correlation with infarct size [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant association of calcium with NIHSS and Barthel Index as noted by Sivasubramaniyam et al in 2017. Ishfaq et al in their study of 138 patients revealed that low levels of serum calcium may be related to more severe clinical findings at the stroke onset [ 14 , 17 ]. A study by Borah et al revealed that total calcium, albumin-corrected calcium, and ionized calcium had a statistically significant negative correlation with infarct size [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 99%